Using reverse engineering to define a domain model - Curado Malta, Mariana (2017)
This chapter presents the early stages of a metadata application profile (MAP) development that uses a process of reverse engineering. The context of this development is the European poetry, more specifically the poetry metrics and all dimensions that exist around this context. This community of practice has a certain number of digital repertoires that store this information and that are not interoperable. This chapter presents some steps of the definition of the MAP Domain Model. It shows how the developers having as starting point these repertoires, and by means of a reverse engineering process are modeling the functional requirements of each repertoire using the use-case modeling technique and are analyzing every database logical models to extract the conceptual model of each repertoire. The final goal is to develop a common conceptual model in order to use it as basis, together with other sources of information, for the definition of the Domain Model.